WARM WATER FOOT SOAK HYDROTHEARPY FOR REDUCING BLOOD PREASSURE - Al Azizah, I'anah (Jurnal Keperawatan GSH, 2024)
Hypertension is a physical condition characterized by systolic blood pressure >140 mmHg and diastolic pressure >90 mmHg. the prevalence of hypertension in Indonesia is 34.1%. Ineffective perfusion is a decrease in blood circulation at the capillary level which can interfere with the body's metabolism. hydrotherapy soak feet in warm water can increase activity (cells) by allowing energy to move through convection (flow through liquid media), causing blood vessels to widen and improve blood circulation throughout the body which causes blood pressure to decrease. The purpose of writing a scientific paper is to find out the implementation of warm water foot soak hydrotherapy to treat hypertension in Mrs. D. The method of scientific writing is in the form of case studies using descriptive research methods. The results of the case study were that after hydrotherapy, soaking feet in warm water for 3 consecutive days, blood pressure decreased, this proves that hydrotherapy, soaking feet in warm water is very influential in the process of lowering blood pressure. Conclusion in the case study of Patient Ny. D has decreased blood pressure. hydrotherapy soak feet in warm water at Mrs. D obtained blood pressure of 150/80 mmHg before 175/100 mmHg. It is hoped that this scientific paper can become a reference in providing implementation in hypertensive patients with ineffective peripheral perfusion management problems.   Hipertensi merupakan kondisi fisik yang ditandai dengan tekanan darah sistolik >140 mmHg dan tekanan diastolik >90 mmHg, berdasarkan dua pengukuran atau lebih. prevalensi hipertensi di Indonesia sebesar 34,1%. Perfusi perifer tidak efektif adalah penurunan sirkulasi darah pada level kapiler yang dapat mengganggu metabolisme tubuh. hydrotherapy rendam kaki air hangat dapat meningkatkan aktivitas (sel) dengan memungkinkan energi bergerak melalui konveksi (mengalir melalui media cair), menyebabkan pembuluh darah melebar dan melancarkan peredaran darah keseluruh tubuh yang menyebabkan tekanan darah menurun. Tujuan penulisan karya tulis ilmiah adalah mengetahui implementasi hydrotherapy rendam kaki air hangat untuk mengatasi hipertensi pada Ny. D. Metode karya tulis ilmiah berbentuk studi kasus yang menggunakan metode penelitian deskriptif. Hasil studi kasus adalah setelah dilakukan tindakan keperawatan hydrotherapy rendam kaki air hangat selama 3 hari berturut-turut tekanan darah menurun, hal ini membuktikan bahwa tindakan hydrotherapy rendam kaki air hangat yang tepat sangat mempengaruhi dalam proses penurunan tekanan darah. Kesimpulan dalam studi kasus Pasien Ny. D mengalami penurunan tekanan darah. hydroterapy rendam kaki air hangat pada Ny. D didapatkan tekanan darah 150/80 mmHg sebelumnya 175/100 mmHg. Saran Karya Tulis Ilmiah ini diharapkan dapat menjadi referensi dalam memberikan implementasi pada pasien hipertensi dengan masalah keperawatan perfusi perier tidak efektif.